CANCEL CULTURE: CYBERBULLYING ON TWITTER SEEN FROM THE SPACE TRANSITION THEORY - Shinta Julianti (Universitas Djuanda Bogor, 2023)
The cancel culture action is a sort of boycott or rejection, as well as other negative actions, as a form of protest against actions that are deemed aberrant in society. However, this becomes a contentious issue when the method of delivery is deviant. There are a few people who simply go along with the cancel culture movement, which evolves into cyberbullying. Space transfer hypothesis is a hypothesis that is used to describe the transfer of individual behavior from the physical to the virtual world. The researcher employs a qualitative approach method with data gathering procedures based on observation on Twitter social media platform, and conducts interviews with research subjects, specifically four Twitter users acting as cancel cultural actors and one informant from the Police Department who handles cybercrimes. According to the study's findings, the characteristics that lead a person to abandon culture in the form of cyberbullying on social media platform Twitter are disappointment, dislike, collision of values and conventions, and inability to regulate oneself. Furthermore, for reasons of flexibility, anonymity, ease of mass mobilization, and lack of scrutiny, the offenders exploited social media Twitter as a space transition to carry out their crimes.